Proceedings of the 15th International ACM SIGACCESS Conference on Computers and Accessibility 2013
DOI: 10.1145/2513383.2513399
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of eyes-free touchscreen keyboard typing

Abstract: Typing on a touchscreen keyboard is very difficult without being able to see the keyboard. We propose a new approach in which users imagine a Qwerty keyboard somewhere on the device and tap out an entire sentence without any visual reference to the keyboard and without intermediate feed back about the letters or words typed. To demonstrate the feasibility of our approach, we developed an algorithm that decodes blind touchscreen typing with a character error rate of 18.5%. Our decoder currently uses three compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…This would allow us to investigate eyes-free touchscreen text entry. In preliminary research [14], we found blindfolded participants could type at over 20 words-per-minute with our decoder recognizing over one-third of sentences with no errors.…”
Section: Future Work and Conclusionmentioning
confidence: 78%
“…This would allow us to investigate eyes-free touchscreen text entry. In preliminary research [14], we found blindfolded participants could type at over 20 words-per-minute with our decoder recognizing over one-third of sentences with no errors.…”
Section: Future Work and Conclusionmentioning
confidence: 78%
“…As touchscreen devices are becoming increasingly popular, a considerable amount of research has been conducted to support eyes-free text entry on touchscreens, including tap typing on an invisible virtual keyboard with one or two fingers [24,34], tap typing on a touchpad with a thumb [13], ten-finger typing on a flat touchscreen [5], and ten-finger typing on the back of a tablet [20]. These research showed that eyes-free text entry was feasible because many users could well-remember the Qwerty layout.…”
Section: Eyes-free Text Entrymentioning
confidence: 99%
“…How can the work we have been focusing on for the past decade [3] be expanded into this new realm? Are we finally at the point where eyes-free text input [7] can become a reality in this new world of novel sensing and expanded mobility?…”
Section: Edge Technologiesmentioning
confidence: 99%